Effect of PbO on the elastic and radiation shielding properties of B2O3–Bi2O3–Al2O3–CuO glasses. (July 2022) - Showahy, A.A.; Elsaman, Reda; Issa, Shams A.M.; El-Denglawey, A.; Saddeek, Yasser B.
Abstract: Investigations of quinary B2 O3 –Bi2 O3 –Al2 O3 –CuO–PbO glasses have been accomplished. The density and the ultrasonic velocities variations were exploited to establish the elastic parameters of the glasses. In addition, a correlation between the ultrasonic parameters and the structural modifications characterized by the FTIR spectra to clarify the function of PbO was achieved. The FTIR spectra suggest that PbO is possibly implanted into the aluminum-borobismuthate network forming [PbO6 ] units, while Bi2 O3 and Al2 O3 affect the network with [BiO6 ] and [AlO6 ] structural units. Furthermore, the changes of the structure and the elastic moduli were understood based on the vibrations of lead, aluminates, bismuthate, and borate structural units on one side and the substitution of high-bond strength B2 O3 via low-bond strength PbO. The results of γ-ray attenuation-coefficients indicate that the values of the mass attenuation coefficient (μm ), effective atomic number (Zeff ), and electron density (Ne ) of the prepared samples increase as a function of PbO content. Additionally, the half-value layer (HVL) and the mean free path (MFP) decrease with increasing PbO content. The glass sample 60.5B2 O3 –20Bi2 O3 –7Al2 O3 –0.5CuO–12PbO (mol%) exhibits the highest values of μm (0.15521 at 356 keV), Zeff (26.67 at 356 keV), and Nel (3.24 at 356 keV) and the lowest elastic moduli (Young's modulus 80.7 GPa and bulk modulus 48.6 GPa). Highlights: Gamma shielding and elastic properties of B2 O3 –Bi2 O3 –Al2 O3 –CuO–PbO have been studied. Increases bulk densities from 5.230 to 5.687 g/cm3. The 60.5B2 O3 –20Bi2 O3 –7Al2 O3 –0.5CuO–12PbO has the best effectiveness shielding against gamma photons. The results are useful in a wide variety of applications, including radiation protection.